Effect of Dietary Fibers on Cecal Microbiota and Intestinal Tumorigenesis in Azoxymethane Treated A/J Min/+ Mice. - Birgitte Moen; Kristi Henjum; Ingrid Måge; Svein Halvor Knutsen; Ida Rud; Ragna Bogen Hetland; Jan Erik Paulsen (PLoS ONE)
Foods naturally high in dietary fiber are generally considered to protect against development of colorectal cancer (CRC). However, the intrinsic effect of dietary fiber on intestinal carcinogenesis is unclear. We used azoxymethane (AOM) treated A/J Min/+ mice, which developed a significantly higher tumor load in the colon than in the small intestine, to compare the effects of dietary inulin (IN), cellulose (CE) or brewers spent grain (BSG) on intestinal tumorigenesis and cecal microbiota. Each fiber was tested at two dose levels, 5% and 15% (w/w) content of the AIN-93M diet. The microbiota was investigated by next-generation sequencing of the 16S rRNA gene (V4). We found that mice fed IN had approximately 50% lower colonic tumor load than mice fed CE or BSG (p<0.001). Surprisingly, all three types of fiber caused a dose dependent increase of colonic tumor load (p<0.001). The small intestinal tumor load was not affected by the dietary fiber interventions. Mice fed IN had a lower bacterial diversity than mice fed CE or BSG. The Bacteroidetes/Firmicutes ratio was significantly (p = 0.003) different between the three fiber diets with a higher mean value in IN fed mice compared with BSG and CE. We also found a relation between microbiota and the colonic tumor load, where many of the operational taxonomic units (OTUs) related to low tumor load were significantly enriched in mice fed IN. Among the OTUs related to low tumor load were bacteria affiliated with the Bacteroides genus. These results suggest that type of dietary fiber may play a role in the development of CRC, and that the suppressive effect of IN on colonic tumorigenesis is associated with profound changes in the cecal microbiota profile.